احكام التسعير وحق الدولة فى التدخل الاقتصادى للسوق من منظور الفقه الاسلامي - Lukman Arake (Jurnal Madania)
The Law and State Authority in Economic Activities on Fixed Price of Market in Accordance with Islamic Jurisprudence. Tas’îr or fixed price often becomes a matter of economic activities in society. This is caused by particular economics agents claiming either they get winnings or losses. To solve this, the government as decision maker should play their rules in deciding fixed price which is fair to all economic agents, involved producers, distributors and consumers. Therefore, this article is aimed at reviewing how the Islamic perspectives on fixed price, and how the government authority, intervention and control regarding to it. Therefore, if government does so, it is believed that the economics transaction is possibly run well in accordance with the norms and existed laws.